Fasciola hepatica infection in schoolchildren of Condebamba district, Cajamarca - Rodríguez-Ulloa, Claudia (2018)
The purpose of this research was to determine the prevalence of Fasciola hepatica and its risk factors in schoolchildren of educational institutions of the primary level of three villages in the district of Condebamba, Cajamarca, Peru. A questionnaire was applied to schoolchildren and their parents or guardians to collect information related to risk factors in schoolchildren. It was evaluated 253 faecal samples of schoolchildren between 6 and 12 years old, using the rapid sedimentation technique modified by Lumbreras to diagnose F. hepatica infection. The prevalence of F. hepatica in Condebamba was 5.1%. There were no significant differences in relation to gender or age group. The risk factors associated with the infection were raising cows and defecating outdoors. The prevalence was moderate in Cauday and Ogosgón villages and null in La Merced.